Cutaneous Hodgkin's disease - Torlone, G... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1993)
A 40-year-old man presented with a one year history of erythematous papules and nodules on the trunk and in the right axilla. Three years earlier, a diagnosis of stage I Hodgkin's disease had been established. Complete remission was achieved following 4 cycles of ABVD (doxorubicin, bleomicin, vinblastine, dacarbazine) combination therapy. Histologic examination of a skin biopsy specimen showed the presence of a diffuse, dense inf ltrate throughout the whole dermis to the subcutaneous tissue. The infiltrate was composed of small lymphocytes, eosinophils, plasmacells and Reed-Sternberg cells. Immunohistochemistry revealed the positivity of neoplastic cells for BerH2 (CD3O) and LeuMl (CDl S) antibodies. Reactivity of small lymphocytes for UCHLl (CD4SRO) was also observed. Routine laboratoryexaminations were withinnormallimits. Bonemarrowbiopsy and instrumental investigations (chest X-ray, computed tomographic scans of abdomen and pelvis) showed no abnormalities. The presence of Epstein-Barrviral (EBV) genome was analysed by polymerase chain reaction (FCR) technique. EBV DNA, however, was not found. Based on histologic and immunohistochemical findings, a diagnosis of secondary cutaneous Hodgkirl s disease was made.
Keywords: Complications; Hodgkin's disease; Immunohistochemistry; Pathology; Secondary; Skin neoplasms